Comparación de la composición corporal de mujeres jóvenes obtenida por hidrodensitometría y tres técnicas de bioimpedancia (2017)
ABSTRACT: Bioimpedance measurement allows quick and safe estimation of the body composition. However, it remains controversial which bioimpedance measurement technique is more exact for calculating the fat mass percentage (%FM). Objective: To compare the %FM obtained with three bioimpedance techniques with hydrodensitometry, as a reference method. Materials and methods: In 31 women, the %FM was assessed by hydrodensitometry with simultaneous lung residual volume measurement and three bioimpedance techniques: hands-to-feet (8-electrodes), hand-to-foot (4-electrodes) and foot-to-foot (4-electrodes). Results: Average age and body mass index were 22.4 ± 2.8 years and 23.6 ± 3.3 kg/m2, respectively. There were no significant differences (p > 0.05) between the %FM obtained by hydrodensitometry (31.4 ± 6.6) and hands-to-feet technique (31.9 ± 5.9). However, hand-to-foot and foot to-foot techniques showed differences (p < 0.05) with the reference method of +1.4 % and -4.9%, respectively. There was a fair agreement between hydrodensitometry and the results obtained with hands-to-feet (Bland-Altman: IC95 %: -6.6; 5.6) and hand-to-foot (Bland-Altman: IC95 %: -8.0; 5.2) techniques. The foot-to-foot measurement showed poor agreement with the reference method (Bland-Altman: IC95 %: -4.7; 14.4). Conclusions: In this group of young women with healthy body weight, the hands-to-feet bioimpedance technique generates body composition values closer to the hydrodensitometry results as compared with the hand-to-foot and foot-to-foot techniques. Additionally, the hands-to-feet technique shows a slightly better agreement with hydrodensitometry than the hand-to-foot and foot-to-foot techniques.